Terapi Seni (Mewarnai dan Menggambar) Membantu Lansia Mengatasi Kecemasan - Eska Riyanti; Pudjiati Pudjiati; Eyet Hidayat; Prayetni Prayetni; Nurdahlia Nurdahlia (Jurnal Keperawatan, 2023)
Psychological disorders in the elderly include dementia, anxiety, sleep disturbances and depression. Anxiety is the most common disorder. Based on data from the Ministry of Health, emotional disorders in the elderly in Indonesia occur 10% in the age range 65-74 years and 13% occur in elderly people aged more than 75 years. Elderly people who experience anxiety need good treatment to reduce their anxiety, otherwise it can cause cognitive damage and depression. Handling to reduce anxiety experienced by providing activities that are positive, interesting and fun. One of them is with art therapy. This study aims to determine the effect of coloring therapy on the anxiety level of the elderly. The sample in this study was 30 people who were taken by purposive sampling. The research design used is descriptive analytic with a quasi-experimental approach. The data analysis test used was univariate, bivariate with paired t-test for the effect of art therapy (coloring and drawing)intervention on the anxiety level of the elderly. The results of the study showed that there was a significant difference in the average anxiety score of the elderly before and after the therapeutic intervention (p value = 0.003) with a difference in the average value decreasing the mean score = 5.03, in addition there was a decrease in the moderate and severe anxiety categories between before and after the intervention. Conclusion: coloring and drawing therapy helps reduce anxiety levels in the elderly.